Development of La0.8Sr0.2MnO3+delta electrocatalysts by Pechini's methods as cathode electrocatalysts in alkaline anion exchange membrane fuel cells - Park, Hee-Young; Park, Sang Hyon; Park, Myeong Sun; Kim, Hyoung-Juhn; Henkensmeier, Dirk; Yoo, Sung Jong; Kim, Jin Young; Ryu, Ji Heon; Jang, Jong Hyun (Elsevier BV, 2016)
As cathode electrocatalysts for alkaline anion exchange membrane fuel cells (AAEMFCs), La0.8Sr0.2MnO3+delta electrocatalysts were synthesized by Pechini's method at various heat treatment temperatures (HTT). With HTT increase from 600 to 900 degrees C, the surface area gradually decreased 30.6 to 6.0 m(2) g(-1), while impurity phase was not detected for all HTrs. The specific activity for the oxygen reduction reaction was analyzed to increase with HTT up to 45.8 +/- 6.4 mu A cm(-2) at 0.8 V vs. RHE, which could be correlated with the Mn e(g) filling increase from 052 (600 degrees C) to 0.70 (900 degrees C). Therefore, the mass activity, which equals to the product of specific activity and surface area, showed maximum value (6.33 +/- 0.63 A g(-1)) at HIT of 700 degrees C. (C) 2016 Elsevier B.V. All rights reserved.